Analysis of Promotional Costs to Increase Revenue at Saung Koffie Hideung Karawang - Salsabila Septiani Putri; Dedi Mulyadi; Santi Pertiwi Hari Sandi (West Science Business and Management, 2024)
One way that can support the company’s operational sustainability is trough promotion. Promotion is a marketing effort made by companies to introduce, convince, and influence consumers to be interested in buying the products or services offered. By promoting the company, the company can increase revenue because it is able to attract consumers to buy the products pffered. The purpose of this study is to understand the various types of promotional costs are able to increase revenue at saung koffie hideung. The method in this research is a qualitative method. This research was conducted in Karawang Regency. The research location is in Tegalwaru Subdistrict, Cintalaksana Village. Information in this study was obtained through primary data collected through the process of interviews, observation, and documentation. Promotion costs can provide good benefits for income, which initially the income received per month was only IDR100.000.000,- but after promoting on social media and the costs incurred were high, the income readhed IDR150.000.000,- or increased by 50% every month, hence the promotion costs. Based on the results and discuccion that saung koffie hideung has carried out various promotions on social media and conducting events at saung koffie hideung. Of the various promotions carried out, the highest promotion was in November-December with each promotional cost incurred of IDR7.450.00 and IDR7.950.00 or up 18% due to using promotioms in the form of instagram social media through the @hallokrw account, using content craetor which is specialized in making advertisements. The way of promotion carried out by saung koffie hideung shows that promotion has a good effect in increasing